Sentinel dominance status influences forager use of social information. (17th February 2016) - Kern, Julie M.; Sumner, Seirian; Radford, Andrew N.
Lay Summary: For dwarf mongoose foragers, adjustment of personal vigilance behavior in the presence of a sentinel (raised guard) depends on sentinel class. Dominant individuals perform more sentinel behavior, gain more experience, and may be more likely to provide higher-quality information than subordinate groupmates. Foragers rely more heavily on vocal information provided by dominant sentinels, reducing their own vigilance and gaining an increase in foraging time during playback of a dominant as opposed to subordinate sentinel. Twitter: @Dwarf_Mongoose Abstract: Animals in social groups can acquire information about the need for antipredator behavior by personally sampling the environment or from information provided by others. Use of such social information is expected to be adjusted according to its reliability, but experimental tests are rare and tend to focus just on alarm calls. We use detailed behavioral observations, acoustic analyses, and playback experiments to investigate how differences in sentinel dominance status affect the behavioral decisions of foraging dwarf mongooses ( Helogale parvula ). Dominant individuals acted as sentinels considerably more often than subordinate group members and used higher sentinel posts for guarding, making them potentially higher-quality sentinels in terms of experience and optimal positioning for predator detection. Surveillance calls produced during sentinel bouts contained vocal information about dominance status. Playback experiments showed that foragers used surveillance calls to detect sentinel presence and identity, and adjusted their vigilance behavior accordingly. When a dominant sentinel was on duty, compared with a subordinate groupmate, foragers increased reliance on social information, gathered less information through personal vigilance, and focused more on foraging. Our study contributes novel evidence that a major benefit of individual- and class-specific vocalizations is the potential to assess differences in caller information quality.